The effect of water molecules on paraquat salts: from physicochemical properties to environmental impact in the Brazilian Cerrado - Aguiar, Antônio S. N.; Costa, Luiz B.; Borges, Igor D.; Aguirre, Gerardo; Tejerina-Garro, Francisco L.; Dutra e Silva, Sandro; Napolitano, Hamilton B. (Frontiers in Chemistry, 2023)
The green revolution model that is followed in the Brazilian Cerrado is dependent on mechanization, chemical fertilization for soil dressing and correction, and the use of herbicides. Paraquat is a methyl viologen herbicide marketed as bipyridylium dichloride salts and used (in low doses) to combat weeds in their post-emergence stage. It is a non-selective pesticide that causes the peroxidation of the lipids that make up the cell membrane, and when it comes into contact with foliage, it results in the death of the plant. The effect of water molecules co-crystalized in Paraquat salt structures was analyzed in anhydrous, dihydrate, and trihydrate forms to understand those physicochemical properties in its redox activity. The frontier molecular orbitals were also carried out using DFT to obtain the chemical reactivity of the bipyridylium cation. Finally, the supramolecular arrangements were evaluated to analyze the physicochemical stability and acquire insights on superoxide anions.